Child Protection According to Tafsir Asy-Sya'rawi and Tafsir Al-Misbah: Analysis of the Al-Quran Surah Al-Isra Verse 31 - Iryana, Yovik (Mashadiruna Jurnal Ilmu Al-Qurân dan Tafsir, 2023)
This paper will examine the protection of children in Islam, especially as outlined in the Tafsir Asy-Sya'rawi by Muhammad Mutawalli Al-Sya'rawi and the Tafsir Al-Misbah by M. Quraish Shihab. This is because both of them are contemporary commentators whose interpretation studies are discussed in social studies. This paper is a library-research with the main sources being Tafsir Asy-Sya'rawi and Tafsir Al-Misbah, in addition to books and journal articles that support secondary sources. This paper concludes that both Al-Sha'rawi and Quraish Shihab prohibit violence and killing of children in their respective interpretations. For Asy-Sya'rawi children are the pearls of life in the future. This is in accordance with the main message of Law Number 23 of 2002 concerning the Protection of Indonesian Children. Meanwhile, in the view of Quraish Shihab, children are a gift from Allah SWT who are born out of nature that must be maintained and developed by their parents. For Quraish Shihab, if the child deviates then it is the fault of the parents. The Qur'an forbids killing children both physically and mentally. Neglecting children's education is part of killing children mentally.